90-2x=-5+3x

Simple and best practice solution for 90-2x=-5+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90-2x=-5+3x equation:


Simplifying
90 + -2x = -5 + 3x

Solving
90 + -2x = -5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
90 + -2x + -3x = -5 + 3x + -3x

Combine like terms: -2x + -3x = -5x
90 + -5x = -5 + 3x + -3x

Combine like terms: 3x + -3x = 0
90 + -5x = -5 + 0
90 + -5x = -5

Add '-90' to each side of the equation.
90 + -90 + -5x = -5 + -90

Combine like terms: 90 + -90 = 0
0 + -5x = -5 + -90
-5x = -5 + -90

Combine like terms: -5 + -90 = -95
-5x = -95

Divide each side by '-5'.
x = 19

Simplifying
x = 19

See similar equations:

| x-40=-5x+50 | | -2.25(x-1.5)(x-6)=0 | | b+28=5b | | c+13=2c | | -x+0.25y-s=-1.75 | | -3x-14=-6x+25 | | 17.5g+8.29=-2(-11.1g-18.48) | | -16+36=-4(x+9) | | (X-4)(x-4)=44 | | 8x-11=5x+11 | | 6(2n+3)=8(5n+2)+3 | | -3(7b+15)=9-18b | | (5-7i)(3-8i)=0 | | 11-15x-7-6x=7 | | 6+26=-4(2x-8) | | -72+5x=-6x+27 | | -19.4m=-7m-4(3m+17.83) | | 11+1=-4(9x-3) | | 13+2(5c*2)=29 | | -2x-13=-5+5 | | 0=.25x+40 | | -16+12w=7+5+10w | | -6x-13=17-x | | 4(2x+7)=-23+43 | | 4x-(5-x)=35 | | 7(2n+3)=7(7n+5)+5 | | 3b-6+1=2-5b | | 9.4u+19.33-14.71=10.4u+7.82 | | 4x-(5-x)=40 | | 9y+2x^2=0 | | -5(8x+5)=-105 | | 20xcubed-4xsquared-72x= |

Equations solver categories